2022
DOI: 10.3390/su14084673
|View full text |Cite
|
Sign up to set email alerts
|

The Promoting Effect of Green Technology Innovations on Sustainable Supply Chain Development: Evidence from China’s Transport Sector

Abstract: This paper analyses direct and indirect mechanisms of the promoting effect of green technology innovation of transport companies on the SSC development. Based on China’s transport sector data, we conduct an empirical study using the LL-FE model. Theoretical and empirical studies have two key findings: (1) On the direct mechanism, green technology innovations of transport companies have a positive role of promoting SSC development. When the level of green technological innovation of transportation enterprises i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Thus, the development of new technologies has a significant impact on greenhouse gas emissions. Li L. and Li W. [33] argued that the green technology innovation of transportation companies promotes the development of SSC in a direct manner. Transport companies' technological innovation increased by 1%, while their carbon dioxide emissions decreased by 0.23%.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the development of new technologies has a significant impact on greenhouse gas emissions. Li L. and Li W. [33] argued that the green technology innovation of transportation companies promotes the development of SSC in a direct manner. Transport companies' technological innovation increased by 1%, while their carbon dioxide emissions decreased by 0.23%.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the importance of the criteria for the transport company's investment in the creation and development of technological infrastructure and the importance of the criteria of the marketing of the transport company for the implementation of the technological development, a study was conducted. Several authors researched the effects of marketing on technological development in transport companies, such as [4,7,14,21,32,33]. This article's authors' hypothesis results are based on an assessment of the importance of the criteria for the transport company's investment in the creation and development of technological infrastructure through quick troubleshooting; adjusting for speed of product delivery; ensuring the continuity of the cargo transportation process; reduction of carbon dioxide; improvement road safety; reduction of congestion; for the introduction of digital transformation; and for the performance of statistical analysis of big data.…”
Section: Discussionmentioning
confidence: 99%
“…Several works of literature have discussed adopting and implementing green initiatives in the transportation industry to protect the environment. Li and Li [ 26 ] recognized that green technology innovation is critical for lowering carbon emissions and achieving long-term development in China's transportation sector. Using the Hausman test, Robustness test, and Fixed Effect (FE) model, they found that green technology innovations of transportation companies have a positive role in promoting South-South cooperation (SSC) development.…”
Section: Introductionmentioning
confidence: 99%